Technical report, Design project 2-IBIO 3870 Electrowrist (2019)
Electrowrist is the solution for the pain in the wrist caused by inflammation of the muscles of the hand causing Carpal Tunnel Syndrome or tendonitis. With our product we can relieve the pain by reducing the swollenness of the transverse carpal ligament using electrostimulation and movement restriction of the ligaments. In Colombia this syndrome is the most common one in the working population causing great expenses to the government and companies.